NUMERICAL INVESTIGATION ON FLEXURAL BEHAVIOR OF RC BEAMS WITH LARGE WEB OPENING EXTERNALLY STRENGTHENED WITH CFRP LAMINATES UNDER CYCLIC LOAD: THREE-POINT BENDING TEST - NOORI, ABDULQADER; Nihad Noori, Abdul Qader; Celik , Tuncer (Journal of Applied Engineering Science, 2022)
In the current paper, the effect of carbon fiber reinforced polymer (CFRP) laminates on the flexural strength of reinforced concrete beam (RCB) with the web opening in the flexural zone was investigated using a numerical method. The main aim of the current work is to model the reinforced concrete beam strengthen by two shapes of CFRP laminates (2- layer and U-shape), to observe the influences of CFRP on the flexural strength of the beam. To this end, cyclic loading was applied to investigate the flexural behaviour of the Twelve RC beams under the cyclic loading. All beams kept the same dimensions length, breadth, and depth (2400 × 300 × 200) mm were modeled in the finite elements adopted by ABAQUS software. Steel bars have been used for both flexural strengthening and stirrups. A Three-point bending tests were performed using cyclic loading. Furthermore, the effect of web openings with different sizes (Side length of 40, 60, 75% of the breadth) on the flexural behavior of RC beams was investigated in detail. The flexural strength, local analysis, and ductility of the base beam and CFRP reinforced beam were analyzed. The results of the simulations revealed that the CFRP laminates enhanced the strength of the base beam significantly.
Keywords: von mises stress, reinforced concrete beam, yielding criteria, carbon fiber reinforced polymer, flexural behavior, cyclic loading, numerical analysis